Roles of Ion and Water Channels in the Cell Death and Survival of Upper Gastrointestinal Tract Cancers - Shiozaki, Atsushi; Marunaka, Yoshinori; Otsuji, Eigo (Frontiers in Cell and Developmental Biology, 2021)
Ion and water channels were recently shown to be involved in cancer cell functions, and various transporter types have been detected in upper gastrointestinal tract (UGI) cancers. Current information on the expression and roles of these channels and transporters in the death and survival of UGI cancer cells was reviewed herein, and the potential of their regulation for cancer management was investigated. Esophageal cancer (EC) and gastric cancer (GC) cells and tissues express many different types of ion channels, including voltage-gated K+, Cl-, Ca2+, and transient receptor potential (TRP) channels, which regulate the progression of cancer. Aquaporin (AQP) 1, 3, and 5 are water channels that contribute to the progression of esophageal squamous cell carcinoma (ESCC) and GC. Intracellular pH regulators, including the anion exchanger (AE), sodium hydrogen exchanger (NHE), and vacuolar H+-ATPases (V-ATPase), also play roles in the functions of UGI cancer cells. We have previously conducted gene expression profiling and revealed that the regulatory mechanisms underlying apoptosis in ESCC cells involved various types of Cl- channels, Ca2+ channels, water channels, and pH regulators. We have also previously demonstrated the clinicopathological and prognostic significance of their expression in ESCC patients, and shown that their pharmacological blockage and gene silencing had an impact on carcinogenesis, indicating their potential as targets for the treatment of UGI cancers. A more detailed understanding of the molecular regulatory mechanisms underlying cell death and survival of UGI cancers may result in the application of cellular physiological methods as novel therapeutic approaches.